2005
DOI: 10.1182/blood-2004-04-1469
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular endothelial growth factor receptor 2–mediated endothelial cell activation by Axl tyrosine kinase receptor

Abstract: GAS6, the product of a growth arrest specific (GAS) gene, is the ligand of the tyrosine kinase receptor Axl. GAS6 and Axl are both expressed in endothelial cells, where they are involved in many processes such as leukocyte transmigration through capillaries and neointima formation in injured vessels. Here IntroductionAxl is a 140-kDa protein which belongs to a subfamily of tyrosine kinase receptor (RTK) that includes also Mer and Rse. These receptors are characterized by the presence of 2 immunoglobulinlike d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 77 publications
7
87
1
1
Order By: Relevance
“…54 In addition, some SH2-containing phosphatases also have been shown to be involved in down-regulating KDR/Flk-1 activation. 55,56 Therefore, it is possible that blocking of VEGF-A-mediated KDR/Flk-1 activation by emodin is through the induction of phosphatases that affect KDR/Flk-1 phosphorylation by VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…54 In addition, some SH2-containing phosphatases also have been shown to be involved in down-regulating KDR/Flk-1 activation. 55,56 Therefore, it is possible that blocking of VEGF-A-mediated KDR/Flk-1 activation by emodin is through the induction of phosphatases that affect KDR/Flk-1 phosphorylation by VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Axl stimulation by the structural homolog of ProS, Gas6, activates SHP2, thereby inhibiting VEGF-A-dependent activation of both VEGFR2 and the angiogenic program in vascular endothelial cells. 29 More recently, Ruan and Kazlauskas demonstrated that VEGF-A-dependent activation of VEGFR2 and recruitment of Src family kinases engages the receptor tyrosine kinase Axl to trigger ligand-independent autophosphorylation that promotes activation of Akt. 41 The evidence we provide for the existence of a ProS/Mer/SHP2 axis, which inhibits VEGF-A-mediated VEGFR2, MAPK Erk1/2, and Akt activation, suggests that, besides Axl, Mer tyrosine kinase receptors is also a .…”
Section: Discussionmentioning
confidence: 99%
“…29 ECs cultured on extracellular matrix preparations, such as Matrigel, spontaneously differentiate into capillary-like structures. 29 To ascertain further the inhibitory effect of ProS on angiogenesis, we next tested its effects in an in vitro morphogenesis assay in which human ECs were cultured on Matrigel. Typical capillary-like structures, formed by ECs cultured on Matrigel, for 24 hours, are represented in Figure 2Ai (by arrows, control).…”
Section: Protein S Inhibits Angiogenesis 5075mentioning
confidence: 99%
See 2 more Smart Citations